Mengulik Makna Kisah Penyaliban Tuhan Dari Bingkai Pemahaman Kaum Pentakostal - Manurung, Kosma (Sekolah Tinggi Teologi Imauel Pacet, 2025)
There are many great and meaningful stories recorded in the Bible and one that is very important for the life of a believer is related to the story of the crucifixion of the Lord. Long before this crucifixion event occurred, the prophets had already announced what the picture of suffering would be like as a result of the event and its impact on human life. This article attempts to explore the meaning of the Lord's crucifixion from the framework of understanding of the Pentecostals. The selection of qualitative descriptive methods and combining them with literature studies is intended to provide a structured, accurate, and in-depth picture related to the Bible's propechy about the Lord's crucifixion, the Lord's crucifixion event recorded by the four Gospels, and the meaning of this crucifixion story for Pentecostals. It is concluded that for Pentecostals, this crucifixion story has a meaning, namely a real manifestation of the peak of God's love for humans, forgiveness of sins in which God's salvation is inherent, an exchange of fate, and an example to follow.